Sistema de soporte a la toma de decisiones para la prevención de brote de antracnosis en un cultivo de tomate (2018)
Anthracnose disease attacks tomato crops causing damage to fruit and minimizing its commercialization. Anthracnose is combated in two ways, on the one hand, the use of highly toxic fungicides combats the disease. Nonetheless, these fungicides affect the health of farmers and consumers. On the other hand, the continuous monitoring of crop conditions prevents the appearance of the disease. However, the prevention of diseases in crops presents an incomplete implementation (i.e., lack of data processing and sending alerts to farmers). Recently, precision agriculture and decision support systems (DSS) are concepts applied to crops to improve their production. In this paper, we propose a DSS to prevent the development of anthracnose in tomato crops (DSSAT). DSSAT collects agroclimatic data from the tomato crop, processes the collected data and generates alerts aimed at preventing anthracnose disease.